The genetics of blood pressure regulation and its target organs from association studies in 342,415 individuals - Ehret, G; McCarthy, M; Ferreira, T; Farrall, M; Goel, A; Watkins, H; Groves, C; Rayner, N (Nature Publishing Group, 2016)
To dissect the genetic architecture of blood pressure (BP) and assess how its elevation promotes downstream cardiovascular diseases, we analyzed 128,272 SNPs from targeted and genome-wide arrays in 201,529 individuals of European ancestry. Genotypes from an additional 140,886 individuals of European ancestry were used as validation for loci reaching genome-wide significance but without prior support in the literature. We identified 66 BP loci, of which 17 were novel and 15 harbored multiple distinct association signals, and which together explain up to 3.5% of BP variation. The 66 index SNPs were enriched for cis-regulatory elements, particularly in vascular endothelial cells, consistent with a primary role in BP control through modulating blood vessel tone and fluid filtration across multiple tissues, not solely the kidney. Importantly, the 66 index SNPs combined in a risk score showed comparable effects in 64,421 individuals of non-European descent (South-Asian, East-Asian and African), confirming that these are ancestral physiological effects that arose prior to human migration out of Africa. The 66-SNP BP risk score was significantly associated with target-organ damage in multiple tissues, with minor effects in the kidney. Our data expand current knowledge of BP pathways, and also, highlight that BP regulation and its effects may occur in multiple organs and tissues beyond the classic renal system.